An experimental and numerical study of slurry erosion behavior in a horizontal elbow and elbows in series. (December 2021) - Wang, Qiuchen; Huang, Qiyu; Wang, Nianrong; Wen, Yunhao; Ba, Xili; Sun, Xu; Zhang, Jun; Karimi, Soroor; Shirazi, Siamack A.
Highlights: The erosion hot spot at lower Reynolds number locates at the intrados of the horizontal elbow. The maximum erosion location changes to the extrados of the elbow when velocity increases. In a two-elbow geometry, erosion rate in the second elbow primarily changes with the length of the straight pipe between the elbows. Abstract: Erosion in elbows is one of the most important issues in pipeline flow assurance for the oil and gas and mining industries. In this study, slurry erosion in a horizontal elbow and elbows in series are numerically and experimentally investigated. The maximum erosion location of horizontal elbow is revealed by conducting slurry erosion painting experiment. The erosion process is then modeled by using computational fluid dynamics (CFD) techniques. The accuracy and stability of the CFD-based erosion model are carefully examined using experimental results. Using the validated numerical methods, the effects of particle concentration, geometry parameter, inlet conditions are investigated. The erosion processes under these different conditions are further analyzed by examining fluid flow development, particle trajectories and impact information. The results of this CFD study present some cautious guidelines for conducting erosion studies of liquid-solid flows and pipeline system designs.